Effect of Metformin on Diabetes Mellitus Prevention in Pregnant Women with Risk Factors - Shirin Niroomanesh; Masoumeh Dadashaliha; Farahnaz Ahmadi; Fatemeh Rahimi Sherbaf; Forough Forghani (Tehran University of Medical Sciences, 2010)
Objective: This study evaluated the efficacy and safety of metformin on prevention of gestational diabetes mellitus in women with high risk of GDM. Materials and methods: Total number of 189 pregnant women aged between 25 to 35, and 10 to 14 weeks pregnancy,admitted to  Mirza Koochakkhan Hospital, Tehran in January 2008 - January 2009 entered to this randomized controlled clinical trial. The women had one of the three risk factors; history of GDM, family history of diabetes, or BMI ≥ 30 kg/m2, with normal results in the glucose challenge test (GCT) or the glucose tolerance test (GTT). Subjects were randomly split to two groups; 63 women (group A) who received metformin (500 mg, twice a day) and 126 women (group B) did not use metformin. Incidence  of gestational diabetes was compared between two groups. Results: The incidence  of gestational diabetes was significantly different between two groups (%1.4 in group A, %15.4 in group B) (p<0.001). The study also showed that the insulin requirement was significantly different between two groups after developing GDM (group A %3.6, group B %9.5, p=0.001). Conclusion: Using Metformin can effectively reduce the incidence of GDM in pregnant women at risk.